Evaluating Violants of Thrifting Policies on Online Platforms: A Public Sentiment Analysis Thorough Instagram - Ami Afriyani; Muhammad Taufiq Hatta Wibowo (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The phenomenon of "thrifting" has become both a lifestyle and an economic lifeline for segments of society particularly small business owners sparking intense public debate when the government reaffirmed restrictions on the import and online sale of used clothing. Within the framework of public policy evaluation, public opinion emerging in digital spaces serves as a form of feedback, reflecting the extent to which a policy is perceived as well-targeted, fair, and responsive to the needs of affected communities. This study employs a mixed-methods approach, combining descriptive analysis in the discussion with quantitative analysis of sentiment data processed from Instagram. Netizen comments were manually collected and subjected to text pre-processing (case folding and data cleaning) before being analyzed using a lexicon-based sentiment analysis method. The results indicate that negative sentiment dominates public opinion at 59%, followed by positive sentiment at 32% and neutral sentiment at only 9%. These findings suggest that the majority of the public views the policy as falling short of criteria regarding adequacy and equity in policy evaluation, as it is perceived to potentially curtail the economic opportunities of small-scale traders and limit public access to affordable, wearable clothing. Nevertheless, a portion of the public supports the policy, viewing it as an effective and appropriate measure to protect the domestic textile industry and curb the influx of illegal products. Theoretically, this study reinforces research on the digital public sphere as an arena for participatory policy evaluation and its relevance to consumer behavior. Practically, the findings are intended to prompt government reflection on improving the effectiveness of policy communication, ensuring greater responsiveness to public aspirations during the implementation process.